2011
DOI: 10.1044/0161-1461(2010/10-0001)
|View full text |Cite
|
Sign up to set email alerts
|

Functional Seating for School-Age Children With Cerebral Palsy: An Evidence-Based Tutorial

Abstract: Seating intervention may produce positive body structure and function, activities, and participation effects for school-age children with CP when appropriate equipment is provided for weight bearing, the pelvis is positioned for stability and mobility, and the body is properly aligned. SLPs can support functional seating for school-age children with CP by communicating with professionals with seating expertise and by invoking and monitoring recommended guidelines for children with basic and complex seating nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…chosen so that the students can work, and enough time has to be given to students to complete tasks-in other words, remedial activities have to be widely used in schools (see also Costigan & Light, 2011;Hutton & Coxon, 2011;Maher et al, 2011). Attention to each student as an individual is at the core of all this (cf., Imms et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…chosen so that the students can work, and enough time has to be given to students to complete tasks-in other words, remedial activities have to be widely used in schools (see also Costigan & Light, 2011;Hutton & Coxon, 2011;Maher et al, 2011). Attention to each student as an individual is at the core of all this (cf., Imms et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Concrete help for students with physical disabilities may include, for example, looking for ways to have a good sitting position and opportunities work at the desk but even this can require a variety of multiprofessional expertise (Costigan & Light, 2011). Being able to work in a good position is also a part of so-called postural treatment, that Hutton and Coxon (2011) call "postural care", and Pountney, Mandy, Green, and Gard (2009) "postural management program".…”
Section: Theoretical Background: How Does Physical Disability Challenmentioning
confidence: 99%
“…The modification of sitting posture changes the structure of respiratory muscles in resting position. Change in sitting posture can enhance the respiratory muscle activities, reduce the risk of airway blockage, and ultimately improve respiratory functions [ 25 , 26 ]. The chair-inclination intervention is an ergonomic approach that can affect posture and also can change function of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…Children with spastic CP, because of their abnormal muscle tone and unstable posture, often display a particular way of sitting. To compensate for their unstable posture, their sitting position involves upper trunk flexion and posterior pelvic tilt [ 26 ]. Studies demonstrated that the anterior seat inclination helped the trunk extend into a more upright position [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…4, p.108). Costigan and Light 5 suggest that seating can be used to enhance body structure and functioning as well as activity and participation. Seating interventions directed at the level of body structure and functioning impairments may, for example, enhance respiratory function, influence muscle tone or reflexes, reduce risk of, or accommodate for, anatomical deformity or address skin interface pressure management.…”
Section: Introductionmentioning
confidence: 99%